T-Cell progenitors as a new immunotherapy to bypass hurdles of allogeneic hematopoietic stem cell transplantation - Gaudeaux, Pierre; Moirangthem, Ranjita Devi; Bauquet, Aurélie; Simons, Laura; Joshi, Akshay; Cavazzana, Marina; Nègre, Olivier; Soheili, Shabi; André, Isabelle (Frontiers in immunology, 2022)
Allogeneic hematopoietic stem cell transplantation (HSCT) is the treatment of preference for numerous malignant and non-malignant hemopathies. The outcome of this approach is significantly hampered by not only graft-versus-host disease (GvHD), but also infections and relapses that may occur because of persistent T-cell immunodeficiency following transplantation. Reconstitution of a functional T-cell repertoire can take more than 1 year. Thus, the major challenge in the management of allogeneic HSCT relies on the possibility of shortening the window of immune deficiency through the acceleration of T-cell recovery, with diverse, self-tolerant, and naïve T cells resulting from de novo thymopoiesis from the donor cells. In this context, adoptive transfer of cell populations that can give rise to mature T cells faster than HSCs while maintaining a safety profile compatible with clinical use is of major interest. In this review, we summarize current advances in the characterization of thymus seeding progenitors, and their ex vivo generated counterparts, T-cell progenitors. Transplantation of the latter has been identified as a worthwhile approach to shorten the period of immune deficiency in patients following allogeneic HSCT, and to fulfill the clinical objective of reducing morbimortality due to infections and relapses. We further discuss current opportunities for T-cell progenitor-based therapy manufacturing, including iPSC cell sources and off-the-shelf strategies. These opportunities will be analyzed in the light of results from ongoing clinical studies involving T-cell progenitors.